2005
DOI: 10.1017/s0950268805005522
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae and Mycoplasma pneumoniae pneumonia: comparison of clinical, epidemiological characteristics and laboratory profiles

Abstract: Short running head: C. pneumoniae and M. pneumoniae pneumonia 2 SUMMARYThe purpose of our retrospective three-year-study was to analyse and compare clinical and epidemiological characteristics in hospitalized patients older than six years with communityacquired pneumonia (CAP) caused by Chlamydia pneumoniae (87 patients) and Mycoplasma pneumoniae (147 patients). C. pneumoniae and M. pneumoniae infection was confirmed by serology. C. pneumoniae patients were older (42.12 year vs. 24.64 year), and were less like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…A study on both children and adults in Yugoslavia revealed that MPP was more frequent between August and November. [18] Another study found that M. pneumoniae infection was more common in winter than other seasons in Istanbul, Turkey. [6] A peak of M. pneumoniae infection in June or July was observed in Italy and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…A study on both children and adults in Yugoslavia revealed that MPP was more frequent between August and November. [18] Another study found that M. pneumoniae infection was more common in winter than other seasons in Istanbul, Turkey. [6] A peak of M. pneumoniae infection in June or July was observed in Italy and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received antibiotic therapy (azithromycin 1×500 mg for 3 days) and were discharged from hospital without complications. We excluded patients with dual infections described in early studies and patients with respiratory infections [13,14]. …”
Section: Discussionmentioning
confidence: 99%
“…[II] A study from Israel reported no distinguishing clinical features for chlamydial pneumonia, except that it affected older patients than pneumococcal and mycoplasma infections 98 . [II] A comparison of C pneumoniae and M pneumoniae confirmed the age difference between the groups and stated that, although clinical features could not be used to distinguish between the two, cough, hoarseness and rhinitis were all more common in M pneumoniae pneumonia 138 . [III] Where C pneumoniae was the only pathogen identified, the illness was generally mild with non-specific symptoms 139 .…”
Section: Section 4 Clinical Featuresmentioning
confidence: 99%